Fabrication Methods of Electroactive Scaffold-Based Conducting Polymers for Tissue Engineering Application: A Review - Asri, Nurul Ain Najihah; Mahat, Mohd Muzamir; Zakaria, Azlan; Safian, Muhd Fauzi; Abd Hamid, Umi Marshida (Frontiers in Bioengineering and Biotechnology, 2022)
Conductive scaffolds, defined as scaffold systems capable of carrying an electric current, have been extensively researched for tissue engineering applications. Conducting polymers (CPs) as components of conductive scaffolds was introduced to improve morphology or cell attachment, conductivity, tissue growth, and healing rate, all of which are beneficial for cardiac, muscle, nerve, and bone tissue management. Conductive scaffolds have become an alternative for tissue replacement, and repair, as well as to compensate for the global organ shortage for transplantation. Previous researchers have presented a wide range of fabrication methods for conductive scaffolds. This review highlights the most recent advances in developing conductive scaffolds, with the aim to trigger more theoretical and experimental work to address the challenges and prospects of these new fabrication techniques in medical sciences.